2015
DOI: 10.1071/mf13346
|View full text |Cite
|
Sign up to set email alerts
|

Important sources of variation to be considered when using fin clips as a surrogate for muscle in trophic studies using stable isotopes

Abstract: White muscle is the prevalent tissue for C and N stable isotope analysis in fish, requiring the death of the fish or biopsy procedures that could lead to infections or severe damage. Given that caudal fin-clipping does not seriously affect growth or condition, the present study assessed the suitability of caudal fin tissue as replacement for muscle tissue in trophic studies. Clips of caudal fin were a useful non-lethal surrogate of muscle samples in four studied reef-fish (Diplodus argenteus, Pagrus pagrus, Ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 39 publications
2
10
0
Order By: Relevance
“…Discrimination factors were calculated as follows: normalΔXitalicdietitalictissue=δXitaliceq.italictissueδXdiet, where Δ X diet − tissue is the DTDF value of δ 13 C or δ 15 N, the δX eq . tissue values are the average isotopic ratios corresponding to the model δX ∞ values in Equation and δX diet is the average delta value for the experimental diet (see Table ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Discrimination factors were calculated as follows: normalΔXitalicdietitalictissue=δXitaliceq.italictissueδXdiet, where Δ X diet − tissue is the DTDF value of δ 13 C or δ 15 N, the δX eq . tissue values are the average isotopic ratios corresponding to the model δX ∞ values in Equation and δX diet is the average delta value for the experimental diet (see Table ).…”
Section: Methodsmentioning
confidence: 99%
“…While congruence in isotopic composition between muscle and fin tissue has been found, some studies have, nonetheless, reported considerable variability in δ 13 C and δ 15 N values that should be considered when using fin tissue as an alternative to muscle tissue. For example, the fin‐muscle relationship has been shown to vary with the diet type, tissue type and size of the fish . These differences are likely to be most pronounced for species that either have a wide prey range, such as omnivores or that are likely to experience seasonal variation in prey availability .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fin‐muscle relationship have been shown to vary with size, space and time (Galván, Funes, Liberoff, Botto, & Iribarne, ), but these factors did not seem to affect our results given that body size variation was low in both species (Longnose Gar = mean SL of 66.5 ± 6.7 cm, Smallmouth Buffalo = mean SL of 49.25 ± 10.2 cm, respectively) and fishes were collected in the same period from the same river reach. Regarding δ 15 N, the regression slopes deviated slightly from a perfect 1:1 relationship (Table ; Figure ), suggesting that fin tissues assimilate N at rates similar to those of muscle tissue in these species.…”
Section: Discussionmentioning
confidence: 89%
“…from copepods to mysids) with the size of juvenile Japanese seabass ( Lateolabrax japonicus ) (Fuji, Kasai, Ueno, & Yamashita, ). Generally, larger individuals have relatively higher δ 13 C and δ 15 N due to size‐based feeding (Galván, Funes, Liberoff, Botto, & Iribarne, ; Jardine, Gray, McWilliam, & Cunjak, ; Willis et al, ). To our knowledge, this study is the first report using stable isotope analysis to demonstrate a diet shift in juvenile Chinese sturgeon.…”
Section: Discussionmentioning
confidence: 99%